Membranas formadas por peptídeos ácido glutâmico (E), fenilalanina (F) e lisina (K): um estudo energético e estrutural via dinâmica molecular - Sousa, Elias Rafael de (2024)
In this work, we developed a theoretical study on four models of peptide membranes formed by the amino acid sequence EF4K, (E) glutamic acid, (F) phenylalanine, and (K) lysine, where two models for the said sequence were created, Model-A and ModelB. Model-B differs by a 180o rotation in dimer 3, which composes the tetramer for membrane formation. The combination of the peptides EF4E and KF4K was carried out, creating two models for the said combination, Model-C and Model-D. In ModelC, the peptides were assembled asymmetrically to form the tetramer, and in Model-D, the peptides were arranged symmetrically to form the tetramer. Our results show, in all cases studied, a packing of the F4 group, characterizing the hydrophobic region of the structure, strongly formed by hydrogen bonds with lifetimes between 1.0 and 1.5 ns, depending on the model under analysis. The alternation in the polar head of the peptide in the nanostructure also strongly contributes to its stability and structural arrangement, demonstrating interactions similar to hydrogen bonds with lifetimes of 1.2–1.5 ns. This high interaction between the EF4K molecules forming the anomembrane is one of the factors ensuring the generation of long structures, as seen experimentally. Results for membranes formed by EF4E and KF4K show that the lifetime of hydrogen bonds (HBs) for Model-D peptides is approximately 12% longer than that observed for Model-C, providing greater rigidity to the former. These results are consistent with those obtained for Coulomb and van der Waals interaction energies and demonstrate that EF4E and KF4K (Model-D) presents better stability compared to EF4E and KF4K (Model-C). The average thickness of the membranes is approximately 1.72±0.06 nm and 2.27±0.02 nm, respectively. Our results also indicate that the EF4E and KF4K (Model-D) structure remains less hydrated in its interior